Análisis de la denominación de origen e indicaciones geográficas en el Ecuador como instrumento de diferenciación y estrategia de comercialización - Carvajal Tocagón, Marcia alexandra (2021)
In this research, the analysis of denominations of origin and geographical indications as value-generating mechanisms of agricultural and artisan products and their impact on commercial strategies was developed\; For which a statistical study of the last five years of Ecuadorian exports of national cocoa, arabic coffee, straw hat, peanuts and pitahaya was carried out, in order to determine the main destination markets for these products and their potential competitors. It was possible to know the degree of implementation in which the six denominations of origin of Ecuador are found and identify the actions that the government takes to potentiate them both nationally and internationally, the government's actions are focused on improving the production and commercialization of the agricultural and artisan services sector in the country through technical assistance, financing and training aimed at small producers through public institutions with MAG, Agrocalidad, Pro Ecuador, BanEcuador, among others.